2006
DOI: 10.1016/j.jinf.2006.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis A virus infections in travelers, 1988–2004

Abstract: Background. Uncertainty exists about the current risk of hepatitis A virus infection in nonimmune travelers to destinations with high or intermediate risk of transmission. We analyzed recent epidemiological data on imported hepatitis A to determine region-specific attack rates and incidences.Methods. Surveillance data on hepatitis A virus infections diagnosed during 1988-2004 were evaluated on the basis of notification by laboratories, additional reports of physicians, and traveler's statistics. This study foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 26 publications
1
15
0
5
Order By: Relevance
“…26 Hepatitis A vaccination should be recommended to all those travelling to countries with high or intermediate risks of hepatitis A. 27,28 Hepatitis A infection constitutes one of the most common VPDs in international travellers. 5,6 The relative risk of hepatitis A for travellers Research Highlights remains significant although there is up to 50 fold decrease of hepatitis A incidence in travellers during the last few years.…”
Section: Discussionmentioning
confidence: 99%
“…26 Hepatitis A vaccination should be recommended to all those travelling to countries with high or intermediate risks of hepatitis A. 27,28 Hepatitis A infection constitutes one of the most common VPDs in international travellers. 5,6 The relative risk of hepatitis A for travellers Research Highlights remains significant although there is up to 50 fold decrease of hepatitis A incidence in travellers during the last few years.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data have shown that the overall risk ratio for HAV in travellers from industrialized to developing countries has decreased from 1:300 to 1:3000 in unimmunized travellers per month of stay [24]. However, the potential of common source outbreaks and subsequent person to person transmission in developing countries with shifting epidemiology continues to expose unprotected travellers to HAV.…”
Section: Targeted Vaccination Strategies For Persons At Increased Rismentioning
confidence: 99%
“…VFRs, especially children, are a major contributor to hepatitis A cases in Europe and North America. Studies from Europe and Quebec have found that VFRs account for 28%-78% of travel-related HA cases (30,32,33,34,35).…”
Section: Hepatitis a And Bmentioning
confidence: 99%